Corporate social responsibility and environmental sustainability: Evidence from India using energy intensity as an indicator of environmental sustainability. Issue 4 (December 2019) - Prasad, Mousami; Mishra, Trupti; Bapat, Varadraj
Abstract: Corporate social responsibility (CSR) expenditure is mandatory for select firms in India. This is an attempt to fix social and environmental responsibility at firm level. As a result of mandated CSR, it is expected that firms will address environmental concerns, which may ensure environmental sustainability. However, the empirical evidence on the role of engagement in CSR and firm's environmental performance is very limited and provides mixed views. This study, therefore, is an attempt to examine the relationship between CSR and one of the environmental sustainability indicators: energy intensity. For this, the study first measures energy intensity using the details of fuel-wise energy consumption. Using the data of 100 firms listed on the Bombay Stock Exchange (BSE) 100 over six years (2009–2010 to 2014–2015), the regression results suggest that at present CSR is not significantly associated with energy intensity. The study has implications for public policy and corporate managers.